The Influence of Auditor Competence And Professional Skepticism on Efforts to Detect Fraud (Survey on Public Accounting Firms in Bandung) - Ali, Muhammad; Kusumaningtyas, Aulia; Noor Bagja, Hafied (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to determine if there is an influence of auditor’s competence and professional skepticism toward efforts to detect fraud. The auditor in conducting an audit of the financial statements, needs to get the necessary trust in the financial statements of all material, whether due to an error or fraud. Fraud is harder to detect than error because it is hidden by the fraudster. The research takes samples with non-probability sampling method using purposive sampling. This research obtained 36 questionnaires from Public Accounting Firms in Bandung. The analysis technique used were validity test, reliability test, classic assumption test, multiple linear regression analysis, and hypothesis test using t-statistic hypothesis test to test partial regression coefficients and F-Statistics to test the simultaneous regression coefficients with 5% significance level. All the statistic calculations are done by using software SPSS 25. The result shows that auditor’s competence and professional skepticism simultaneously influence fraud detection effort significantly. Partially, auditor competence and professional skepticism have a significant influence towards fraud detection effort.